Broadleaf weed control and white clover response to florpyrauxifen-benzyl + 2, 4-D and common pasture herbicides. (14th October 2022) - Greene, Wykle C.; Hagood, Scott; Tracy, Benjamin; Abaye, Ozzie; Flessner, Michael L.
Abstract: The combination of florpyrauxifen-benzyl + 2, 4-D is a new, pre-packaged herbicide mixture for use in pastures and hayfields in the United States. Unlike many other pasture herbicides, florpyrauxifen-benzyl + 2, 4-D is reported to preserve white clover. However, limited research exists on the efficacy of florpyrauxifen-benzyl + 2, 4-D on common weed species and on the level of tolerance of white clover to it. Field trials were conducted in Virginia in 2018 to 2020 to evaluate control of various broadleaf weeds with florpyrauxifen-benzyl + 2, 4-D compared to other commonly used herbicides. Field and greenhouse studies were also carried out to assess white clover tolerance. Weed species evaluated included bulbous buttercup, Canada thistle, horsenettle, and broadleaf plantain. Florpyrauxifen-benzyl + 2, 4-D provided 75% to 99% control of all weeds 90 d after application except for horsenettle (56%), while causing the least white clover injury of any herbicide treatment that was evaluated. Spring herbicide applications resulted in greater bulbous buttercup control compared to fall applications, but florpyrauxifen-benzyl + 2, 4-D provided greater than 81% control from both application timings. There were no differences in aboveground biomass between white clover varieties; however, all herbicides reduced white clover biomass compared to a nontreated control. This research suggests that florpyrauxifen-benzyl + 2, 4-D can improve overall forage quality by controlling broadleaf weeds in mixed grass-legume stands while preserving white clover.